COMBAT OPERATIONS IN MOUNTAINOUS AREAS OF ABKHAZIA DURING THE BATTLE FOR THE CAUCASUS OF 1942-1943 MARUCH DIRECTION. I STAGE - N. I. Medvenskiy (Гуманитарные и юридические исследования)
The article touches upon the preconditions, general course and the outcome of the first stage of combat operations in Maruch direction during the battle for the Caucasus of 1942-1943, the composition and the size of Soviet and German forces as well as the peculiarities of warfare in mountainous terrain.